The significance of sentinel lymph node micrometastasis in breast cancer: Comparing outcomes with and without axillary clearance. (December 2016) - Youssef, Mina M.G.; Cameron, Diane; Pucher, Philip H.; Olsen, Sisse; Ferguson, Douglas
Abstract: Background: Management of micrometastasis in the sentinel node is a controversial topic. Most of the guidelines don't recommend further axillary treatment if micrometastasis are the only finding in the sentinel node. However, some evidence suggests that micrometastasis have significant effect on long term outcomes and therefore indicate systemic treatment. Method: Retrospective cohort study reviewing the management of patients with micrometastasis in the sentinel nodes. Two groups were compared, those who had further axillary clearance and those who had not. The primary endpoints were loco-regional recurrence and lymphedema rate. The secondary endpoints were distant metastasis rate, OS and DFS. Results: 95 patients were found to have micrometastasis or ITC in the axillary SNB over a period of 10 years. Of those, 38 patients had axillary clearance after SNB, while 57 did not. Lymphedema rate was 18.4% in the axillary clearance group versus 0% in the no axillary clearance group (p < 0.001). The LRR event was rare therefore not compared. Distant metastasis rate was 7.01% in the SNB group versus 2.6% in the axillary clearance group. There were no mortalities in the axillary clearance group. This compares to 7.01% among the patients who didn't have axillary clearance. All the patients who died had developed distant metastasis as a cause of death. There was a difference in OS between the two groups in favor of the axillary clearance group (p = 0.004). Discussion: Although not an indication for axillary clearance recent guidelines, micrometastasis and ITC found in the SNB are a sign of a biologically different disease. This important information should be taken in consideration when planning the adjuvant treatment in those patients among other factors considered.